Waldensians in the inquisition record of Jacques Fournier - Baigent, Jack (2021)
The current study aims to provide a dedicated analysis of the depositions of the four Waldensians that appear in the inquisition record of Jacques Fournier, and use this evidence to increase our understanding of Waldensians in the period, and of clandestine heterodox groups more broadly. This unique and detailed source material has been thus far underutilised in histories of Waldensianism, and this thesis hopes to fill a gap in the literature by placing the source under the lens of modern interpretative techniques. The work will be divided into three sections of two chapters each. Section one will focus on the text itself and its evidence, providing an in-depth analysis of the source which will be used as the basis for later chapters. The first chapter will consider the depositions in terms of their production, by focusing on Fournier and his inquisition, his presuppositions, goals and strategies in producing the final record. After peeling back this layer of inquisitorial discourse, the second chapter will seek to provide as complete an account as possible of the evidence in the Waldensians’ depositions. This will cover their strategies for approaching the interrogations, their religious beliefs, and the structure and nature of the movement they were part of. Section two will use this evidence in conjunction with specific interpretative lenses to deepen our understanding of it. Chapter three focuses on gender in the depositions, including a discussion on the potential evidence for Sisters in the Order, and a sketch of the gendered roles which operated within the movement. Chapter four will present an analysis of the spatial components of the testimony, and how the deposition evidence relates to the movements and spatial organisation of underground heterodox groups. Finally, section three will attempt to better place this group of Waldensians in their proper historical context via two comparative analyses. Chapter five will assess the importance of the ideas of Durand of Huesca, a prominent early Waldensian, to later groups operating in the same region. This chapter will demonstrate the existence and importance of cultural memory to Waldensian identity, and that the ideas of Raymond and his companions did not exist in a vacuum. Similarly, chapter six will look into the similarities between these ideas and those of the Spiritual Franciscans, another heterodox group active in the same time and place as the Waldensians. This chapter will investigate their parallel histories and ideas, and show that – although distinctly separate – the two groups were very much part of the same religious culture specific to the region at that time.